2012
DOI: 10.1103/physreva.85.052506
|View full text |Cite
|
Sign up to set email alerts
|

Polarizabilities ofSi2+: A benchmark test of theory and experiment

Abstract: We have calculated electric-dipole polarizabilities of the 3s 2 1 S0, 3s3p 3 P0, and 3s3p 1 P1 states of the Si 2+ ion using recently developed configuration interaction + all-order method. Detailed evaluation of the uncertainties of the final results is carried out. Our value for the ground state electric-dipole polarizability 11.670 (13)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…for a number of divalent systems and Tl [6][7][8][9][10][11][12]. However, the various types of the corrections to the effective dipole operator D eff are included in a more complete way in the CC approach at the present time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…for a number of divalent systems and Tl [6][7][8][9][10][11][12]. However, the various types of the corrections to the effective dipole operator D eff are included in a more complete way in the CC approach at the present time.…”
Section: Methodsmentioning
confidence: 99%
“…It has been tested on a variety of divalent systems [7][8][9][10][11] and applied to Tl [12]. However, there are far less experimental benchmark experiments for the properties of the divalent and trivalent systems in comparison with the alkalis.…”
Section: Introductionmentioning
confidence: 99%
“…A rough estimate of the uncertainties in the B + polarizabilities is possible by reference to similar calculations for the Si 2+ ground state [16]. A CICP calculation gave 11.688 a 3 0 , a revised analysis of a resonant excitation Stark ionization spectroscopy (RESIS) experiment gave 11.669 a 3 0 [16,56], and a CI+MBPT calculation gave 11.670(13) a 3 0 [57]. The comparison between the RESIS and the CICP polarizabilities suggested that a conservative estimate of the ground state 3s 2 1 S e polarizability was 0.25% while that for the excited states was 0.5%.…”
Section: The B + and B 2+ Polarizabilitiesmentioning
confidence: 99%
“…So it is possible that part of the discrepancy with the CI+MBPT calculation could be removed by using the experimental energy difference when calculating the polarizability of the resonant transition. It should be noted that experimental energy differences were used in a recent CI+MBPT calculation of the polarizability of the 3s 2 state of Si 2+ [57]. The present CICP calculation of the ground state polarizability does not take into consideration the contribution from the 2s 2 1 S e → 2s2p 3 P o 1 transition.…”
Section: Comparisons For Almentioning
confidence: 99%
“…The CI+all-order method was used to accurately evaluate properties of atomic systems with two to four valence electrons [9][10][11][12][13][14][15][16], including superheavy elements No, Lr and Rf [17]. An advantage of this approach is an ability to include core correlations for all core shells together with the accurate description of the valence electronic correlations.…”
Section: Introductionmentioning
confidence: 99%